A DIFFERENTIATED DIDACTIC APPROACH TO TEACHING THE ARTS (D.D.A.T.A.) FOR THE PURPOSES OF SPECIAL EDUCATION AND TRAINING - Makris, Ioannis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The goal of the present work is to present the key of pedagogical and didactical principles involved in the differentiated teaching of such arts as music and dance for the purposes of Special Education and Training (Makris, 2019). The paper also will link that differentiated approach with Positive Psychology and, more specifically, with the P.E.R.M.A. model developed by Positive Psychology founder M. Seligman (Slavin, Schindler et a.l., 2012); and with M. Apter’s Reversal Theory (Makris, 2009).At this presentation, we will be presenting didactical principles, methodological tools and case studies deriving from our clinical work that we carried out for 7 years (2012-2019) with mentally challenged individuals (Makris, 2019). In this study also we will have the chance to focus in teamwork teaching so that we may comprehend the principles of that approach experientially. What is more, this work will also focus on potential fields offering themselves for future academic research.